Andrzej Nowakowski, Powszechna historia państwa w zarysie - Mrówczyński, Marek (Czasopismo Prawno-Historyczne, 1992)
Recenzja: Andrzej Nowakowski, Powszechna historia państwa w zarysie, Białystok, b.d.w.